2011
DOI: 10.1007/s10637-011-9777-3
|View full text |Cite
|
Sign up to set email alerts
|

Thymoquinone reduces migration and invasion of human glioblastoma cells associated with FAK, MMP-2 and MMP-9 down-regulation

Abstract: Glioblastoma represent the most frequent primary tumors of the central nervous system and remain among the most aggressive human cancers as available therapeutic approaches still fail to contain their invasiveness. Many studies have reported elevated expression of the Focal Adhesion Kinase (FAK) protein in glioblastoma, associated with an increase in the rates of both migration and invasion. This designates FAK as a promising target to limit invasiveness in glioblastoma. Thymoquinone (TQ), the main phytoactive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
47
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(54 citation statements)
references
References 48 publications
7
47
0
Order By: Relevance
“…Since then, increasing numbers of studies have focused on TQ in cancer therapy. Numerous in vitro and in vivo studies have investigated the antitumor activity of TQ in several types of cancer (6,14,19,(27)(28)(29)33). In tumor protein p53-null myeloblastic leukemia HL-60 cells, TQ induced apoptosis through an intrinsic signaling pathway (34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, increasing numbers of studies have focused on TQ in cancer therapy. Numerous in vitro and in vivo studies have investigated the antitumor activity of TQ in several types of cancer (6,14,19,(27)(28)(29)33). In tumor protein p53-null myeloblastic leukemia HL-60 cells, TQ induced apoptosis through an intrinsic signaling pathway (34).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the antitumor and anticarcinogenic activities of TQ in numerous types of cancer, including breast cancer, glioblastoma and lymphoma (27)(28)(29). In order to elucidate the molecular mechanisms underlying the function of TQ, the effect of TQ on colon cancer cells was examined in the present study.…”
Section: Effect Of Tq On the Viability Of Colon Cancer Cellsmentioning
confidence: 99%
“…Indeed, FAK regulates the turnover of adhesion molecules and drives cell movement [5]. Downregulation and inhibition of FAK protein, which efficiently prevent migration of cancer cells, have been demonstrated in many in vitro and in vivo studies [23][24][25]. Phosphorylated FAK (pFAK), an active form of FAK, is also shown to be essential for an activation of cell protrusions mediated by Rac1 and Cdc42 proteins [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…MMPs, members of the neutral endopeptidase family that can catalyze the degradation of ECM components, are thought to play an important role in tumor invasion and metastasis in colon carcinoma and many other human cancers, and their action in tumors is inhibited by specific tissue inhibitors (TIMPs) (61,62). In our present western blot analysis results, CFZ alone or combined with CPT-11 diminished MMP1 and MMP9 protein expression, while it increased the TIMP1 protein levels in SW620 cells, which was correlated with the invasion and migration inhibition function of CFZ.…”
Section: Discussionmentioning
confidence: 99%